Management of ectopically erupting permanent molars in a seven year old girl. A Case Report. - Meng, Mingmei; Zhou, Xuedong; Zhang, Qiong; Zou, Jing (Journal of the Pakistan Medical Association, 2022)
Ectopic eruption of permanent first molar is a developmental disturbance, leading to many local problems, such as premature loss of the second primary molars, space loss, increased prevalence of dental caries, supraeruption of the opposing molars, mesial inclination of the permanent maxillary first molars and class II molar relationship. We report the case of a seven-and-a-half-year-old girl with ectopic eruption of permanent maxillary and mandibular first molar, treated by orthodontic separators and slicing the distal surface of the adjacent primary second molar separately. Regular examination and timely interception are important during oral health management of children and is of great significance in alleviating the side effects of ectopic eruption. Keywords: Dental management, Ectopic eruption, Permanent first molars